2015
DOI: 10.1155/2015/106157
|View full text |Cite
|
Sign up to set email alerts
|

The Resin fromProtium heptaphyllumPrevents High-Fat Diet-Induced Obesity in Mice: Scientific Evidence and Potential Mechanisms

Abstract: Herbal compounds rich in triterpenes are well known to regulate glucose and lipid metabolism and to have beneficial effects on metabolic disorders. The present study investigated the antiobesity properties of resin from Protium heptaphyllum (RPH) and the possible mechanisms in mice fed a high-fat diet (HFD) for 15 weeks. Mice treated with RPH showed decreases in body weight, net energy intake, abdominal fat accumulation, plasma glucose, amylase, lipase, triglycerides, and total cholesterol relative to their re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 41 publications
0
12
0
1
Order By: Relevance
“… 23 In mice, the HFD induced an elevation of IL-6 after 2, 4 and 6 months, 24 and an increase in plasma levels of pro-inflammatory mediators TNF-α, IL-6 after 15 weeks. 25 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 23 In mice, the HFD induced an elevation of IL-6 after 2, 4 and 6 months, 24 and an increase in plasma levels of pro-inflammatory mediators TNF-α, IL-6 after 15 weeks. 25 …”
Section: Discussionmentioning
confidence: 99%
“…Obesity is also associated with an impairment of endothelial cell function and promotes endothelial dysfunction through an array of metabolic disorders including the accumulation of adipose tissue, high blood pressure, dyslipidemia and diabetes, which are linked to vascular oxidative stress. 25 The endothelium comprises the inner lining of blood vessels, and forms the interface between the circulating blood and the vascular wall. It also acts as an endocrine and paracrine organ, which regulates vascular function by secreting a variety of trophic and vasoactive factors that regulate vascular tone, cell adhesion, smooth muscle cell proliferation and inflammation of the vascular wall.…”
Section: Discussionmentioning
confidence: 99%
“…The remaining mice consumed HFD (HFD control), HFD+FA (0.05% in drinking water, which is equivalent to 10 mg/kg of body weight based on water consumption), or HFD+SIB (0.05% in drinking water, which amounts to 10 mg/kg of body weight) for 15 weeks. FA and SIB concentrations were based on our previous experiments (8,19). FA was suspended initially in 3% (v/v) Tween 80 and then further diluted in water.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have demonstrated the potential of triterpenoids from olive oil as a therapeutic strategy in preventing vascular injury and the progression of cardiovascular diseases (Xiang et al 2012). We have previously reported on the anti-obesity and hypolipidemic properties of the resin from Protium heptaphyllum and its major triterpenoid constituents, alphaand beta-amyrin (AMY), in mice subjected to an HFD for 15 weeks (Carvalho et al 2015;Carvalho et al 2017). We have previously demonstrated the anti-obesity and pro-weight-loss potential of AMY, largely attributed to its modulatory effects on various hormonal and enzymatic secretions related to fat and carbohydrate metabolism and to the regulation of obesityassociated inflammation (Carvalho et al 2015); however, whether AMY can offer protective effects against the influences of obesity on vascular reactivity has not been established.…”
mentioning
confidence: 99%
“…We have previously reported on the anti-obesity and hypolipidemic properties of the resin from Protium heptaphyllum and its major triterpenoid constituents, alphaand beta-amyrin (AMY), in mice subjected to an HFD for 15 weeks (Carvalho et al 2015;Carvalho et al 2017). We have previously demonstrated the anti-obesity and pro-weight-loss potential of AMY, largely attributed to its modulatory effects on various hormonal and enzymatic secretions related to fat and carbohydrate metabolism and to the regulation of obesityassociated inflammation (Carvalho et al 2015); however, whether AMY can offer protective effects against the influences of obesity on vascular reactivity has not been established. It is well known that endothelial dysfunction plays an essential role in the initiation of the cascade of events leading to cardiovascular risk factors (Reriani et al 2010), and a number of pathological conditions are associated with endothelial dysfunction, including diabetes, dyslipidemia, and obesity (Boger et al 1997;Virdis et al 2013;Wilk et al 2013).…”
mentioning
confidence: 99%